Effect of vitamin C on the growth of experimentally induced endometriotic cysts. Issue 7 (30th May 2013) - Durak, Yildirim; Kokcu, Arif; Kefeli, Mehmet; Bildircin, Devran; Çelik, Handan; Alper, Tayfun
Abstract Aim The aim of this study was to investigate the effect of vitamin C on the growth of experimental endometriotic cysts. Material and Methods The endometrium of the uterine horn wall (diameter, 4 mm) was implanted onto the inner surface of the anterior abdominal wall of 40 Wistar albino adult female rats, by laparotomy. The day after the implantation, the rats were randomly assigned into four groups (control group and experimental groups [V1, V2, and V3]) comprising 10 rats each. For 6 weeks, the control group (Group C) received 1 mL distilled water, whereas the experimental groups (Groups V1, V2, and V3) received 0.5 mg, 1.25 mg, and 2.5 mg of vitamin C in 1 mL of distilled water, respectively. The doses were given via oral gavage once per day. At the end of the administration, a second laparotomy was performed and endometriotic cyst volumes and weights of rats among the groups were compared. In addition, the stromal and glandular tissue and the natural killer cell contents of the cysts were compared among the groups. Results The cyst volume in Group V3 and the cyst weights in Groups V2 and V3 were significantly lower than those in Group C. The natural killer cell content in Groups V1, V2, and V3 was significantly lower than that in Group C. Stromal and glandular tissue contents of the groups were not significantly different. Conclusions The dose‐dependent vitamin C supplementation significantly reduced the volumes and weights of the endometriotic cysts.